Building customer loyalty for light steel products “Kencana Truss” in Bali - Wijaya, I Komang Adi Dana; Suprapti, Ni Wayan Sri (International research journal of management, IT and social sciences, 2019)
The purpose of this study is to explain the effect of product quality on customer satisfaction mediated by brand image and brand trust, ultimately determining customer loyalty. The questionnaire distributed 175 copies to the users of Kencana Truss light steel in Bali Province, but valid for processing 133 copies. Data were analyzed using SEM (Structural Equation Modeling) analysis technique. The results of this study found that variable product quality, brand image, and brand trust have a significant positive effect on customer satisfaction. Customer satisfaction variables have a significant positive effect on customer loyalty. Variable brand image and brand trust, significantly mediate the effect of product quality on customer satisfaction. Similarly, customer satisfaction mediates the effect of brand image and brand trust on customer loyalty. The implications of the results of this study indicate that product quality is found as a major factor in increasing customer satisfaction which ultimately results in customer loyalty. Providers of light steel products should pay special attention to product quality, so customer satisfaction and loyalty can be maintained.